Incidence and severity of corynespora leaf fall (CLF) disease of rubber in costal Karnataka and North Malabar region of Kerala - Manju M J; Idicula S P; Jacob C K; Kothandaraman R; Prem E; Suryakumar M; Vinod K K (Indian Journal of Natural Rubber Research, 2001)
Widespread incidence of Corynespora leaf fall (CLF) disease in mature rubber plantations was reported in 1996 from Nettana in South Karnataka, India. Surveys carried out in costal Karnataka and North Malabar region of Kerala during 1998-2000 disease seasons indicated that the disease incidence and severity of infection varied between light to severe in all the locations. The intensity of infection was found to increase gradually and the incidence to widen year after year. Subramanya rerion in Karnataka exhibited maximum intensity of the disease. Fresh incidence was noticed in Hosdurg and Nileshwar in Kerala during 2000. Variation in intensity of disease among different clones was observed with the clone RRII 105 showing high and RRIM 600 and GT 1 showing low infection in all the locations surveyed.
Keywords: Corynespora cassiicola; Hevea brasiliensis; India; Leaf fall disease